Use of dermal fat grafts for treating anetoderma with lipoatrophy following involution of hemangiomas. Issue 4 (22nd May 2020) - Nomura, Tadashi; Nakasone, Mika; Okamoto, Takako; Ejiri, Hirotaka; Osawa, Sayuri; Hashikawa, Kazunobu; Terashi, Hiroto
Abstract: Infantile hemangioma (IH) is a benign vascular tumor that gradually involutes over several years. Rapidly involuting congenital hemangioma (RICH) is the relatively rare congenital vascular tumor that is fully grown at birth and does not undergo postnatal growth and involutes during the first year. However, after involution of both IH and RICH, some have severe sequelae, such as redundant skin or conspicuous scarring, requiring additional treatment. We present the case of a 6‐year‐old girl with a concave deformity due to subcutaneous atrophy, skin darkening, and altered skin texture of her left zygomatic region following involution of a hemangioma. We successfully treated this patient by transferring a dermal fat graft. This technique can be beneficial for atrophic sequelae after regression of a hemangioma and is easy to perform and cosmetically effective.